MyJomChangeYourHabit: An Android Application for Quitting Bad Habit - Asaari, Azrul; A. Mostafa, Salama (Applied Information Technology And Computer Science, 2021)
: Bad habit is a problem that all person in the world will face in their life. Bad habit is a bad lifestyle whether its physical or mental. Such an example smoking, pornography addict, smartphone addict and social media addict. Nowadays there is so many peoples that have so many bad habits in their normal life. The bad habit also can come from the smartphone itself. This application aim is to help the user to reduces or stop themselves from their bad habit. This report will explain about the process in making the MyJomChangeYourHabit. Methodology that was used for this application development is Object-Oriented Methodology. This object-oriented methodology has six phases that is Requirement, analysis, modelling, design, implementation, and lastly evaluation. At the end of this projects the MyJomChangeYourHabit application will finish and can be used by all the people. This application can help other people who have problem with the bad habit to change themselves.